Developing a core set of patient-reported outcomes in pancreatic cancer: A Delphi survey. (April 2016) - Gerritsen, Arja; Jacobs, Marc; Henselmans, Inge; van Hattum, Jons; Efficace, Fabio; Creemers, Geert-Jan; de Hingh, Ignace H.; Koopman, Miriam; Molenaar, I. Quintus; Wilmink, Hanneke W.; Busch, Olivier R.; Besselink, Marc G.; et al.
Abstract: Background: Patient-reported outcomes (PROs) are amongst the most relevant outcome measures in pancreatic cancer care and research. However, it is unknown which out of the numerous PROs are most important to patients and health care professionals (HCPs) in this setting. The aim of this study was to identify a core set of PROs to be incorporated in a nationwide prospective multidisciplinary pancreatic cancer registry. Patients and methods: We performed a two-round Delphi survey among 150 patients diagnosed with pancreatic or periampullary cancer (treated either with curative intent or in palliative setting) and 78 HCPs (surgeons, medical oncologists, gastroenterologists, radiotherapists, nurses, and dietitians) in The Netherlands. In round 1, participants were invited to rate the importance of 53 PROs, which were extracted from 17 different PRO measures and grouped into global domains, on a 1–9 Likert scale. PROs rated as very important (score 7–9) by the majority (≥80%) of curative and/or palliative patients as well as HCPs were considered sufficiently important to be incorporated in the core set. PROs not fulfilling these criteria in round 1 were presented again to the participants in round 2 along with individual and group feedback. Results: A total of 97 patients (94%) in curative-intent setting, 38 patients (81%) in palliative setting and 73 HCPs (94%) completed both rounds 1 and 2. After the first round, 7 PROs were included in the core set: general quality of life, general health, physical ability, satisfaction with caregivers, satisfaction with services and care organisation, coping and defecation. After the second round, 10 additional PROs were added: appetite, ability to work/do usual activities, medication use, weight changes, fatigue, negative feelings, positive feelings, fear of recurrence, relationship with partner/family, and pancreatic enzyme replacement therapy use. Conclusion: This study provides a core set of PROs selected by patients and HCPs, which may be incorporated in pancreatic cancer care and research. Validation outside the Dutch context is recommended for generalisation and use in international studies. Highlights: Patient-reported outcomes (PROs) are among the most relevant outcome measures. It is unknown which out of the numerous PROs are most important in pancreatic cancer. This two-round Delphi survey included 150 patients and 78 health care professionals (HCPs). A total of 17 PROs were selected by both patients and HCPs. This core set of PROs may be incorporated in pancreatic cancer care and research.